Bearing capacity enhancement of footings using confining inclined micropiles: Experimental and analytical investigation - Husain Abbas; Abdullah Almajed; Esmatullah Kotwal; Yousef Al-Salloum (Case Studies in Construction Materials)
Improving the bearing capacity (BC) of existing footings is usually a challenging task. Most of the methods employed are either cumbersome or are not efficient and effective. In the present study, the confinement provided by equally spaced inclined micropiles around a square footing is used to improve the BC of footing. Three angles of inclination with horizontal, viz. 90°, 105°, and 120° of micropiles provided at spacings of 0.33 B and 0.23 B (B is the size of square footing) were investigated. Including the control footing with no micropiles, seven footings were tested under uniformly incrementing quasi-static load. The test results reveal significant enhancement in BC of footing confined by micropiles, which increases with the increase in the inclination of micropiles and with the reduction in the spacing of micropiles. For the micropile spacing of 0.33 B, the enhancement in the BC of footing varied from 14.7 % to 44.2 %, which was enhanced to 26.3–56.5 % for the micropile spacing of 0.23 B. Based on the validation with the test results, an analytical procedure is developed for the design of confinement scheme using inclined micropiles to enhance the BC of shallow isolated footings. An example is also provided for assessing the BC enhancement and footing settlement due to the confining micropiles provided around a shallow rectangular footing.